EXPLORING THE EVOLUTION AND IMPACT OF ATTITUDES TOWARDS WOMEN'S RIGHTS: A MULTIDIMENSIONAL ANALYSIS (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
The topic of women's rights has garnered significant attention across various academic disciplines, social movements, and policy debates. Understanding societal attitudes towards women's rights is crucial for comprehending the progress and challenges in achieving gender equality. This thesis aims to explore the evolution, characteristics, and impacts of these attitudes through a multidisciplinary lens, encompassing historical, cultural, social, economic, and political dimensions.